Predictive circulating biomarkers of the response to anti‐PD‐1 immunotherapy in advanced HER2 negative breast cancer - Yuhan Wei; Hewei Ge; Yalong Qi; Cheng Zeng; Xiaoying Sun; Hongnan Mo; Fei Ma (Clinical and Translational Medicine)
Abstract Background Immunotherapy shows promise for treating advanced breast cancer, but only a few patients could respond. Predictive biomarkers from peripheral blood are urgently needed. Methods We designed a comprehensive 42‐marker mass cytometry panel to profile the peripheral blood samples from 57 patients diagnosed with advanced HER2‐negative breast cancer receiving anti‐PD‐1 combination therapy. Patients were categorized as responders and non‐responders according to 6‐month progression‐free survival (PFS), followed by phenotypic and functional comparations to identify candidate predictive biomarkers. Longitudinal analysis of paired samples further revealed dynamic changes in these specific subpopulations. Results Non‐responders exhibited significantly higher frequencies of CD39+ Tregs (adjusted p = .031) in the T‐cell milieu at baseline, which exhibited a positive correlation with PD‐1+ T cells in the NR group. Longitudinal assessment indicated a significant decrease of PD‐1+ T cells and an increase of CD39+ Tregs following anti‐PD‐1 treatment, suggesting their potential role in immunotherapy resistance. In the myeloid compartment, responders showed significantly higher CCR2+ monocyte‐derived dendritic cell frequencies than non‐responders (adjusted p = .037). These cells were positively correlated with other dendritic cells in responders but negatively with naïve T cells in non‐responders. Based on these two efficacy‐related biomarkers, we developed an immunotherapy prognostic prediction model and confirmed its superiority in distinguishing patient PFS (p < .001). Conclusion Peripheral CD39+ Tregs and monocyte‐derived dendritic cells are correlated with immunotherapy response, serving as potential biomarkers to guide therapeutic choices in immunotherapy. Key points CD39+ Tregs in peripheral blood are associated with poor response to anti‐PD‐1 immunotherapy in advanced breast cancer. Higher frequencies of CCR2+ monocyte‐derived dendritic cells correlate with better immunotherapy outcomes. A predictive model based on CD39+ Tregs and monocyte‐derived dendritic cells effectively distinguishes patient progression‐free survival. Peripheral blood biomarkers offer a non‐invasive approach to guide immunotherapy choices.